Enhancing Sports Facilities and Strengthening Physical Education Programs in Public Colleges - Shyam Prasad Sedai,; Suresh Jung Shahi, (Journal of Balkumari College, 2025)
Engagement in physical activity plays a crucial role in enhancing cognitive function, attention span, classroom behavior, and academic achievement. Regular participation in sports and exercise enhances concentration, academic performance, and overall well-being. Despite its importance, Nepal faces significant challenges in sports infrastructure and physical education, necessitating strategic investments and planning to improve facilities, trained personnel, and student engagement. This study evaluates the sports facilities and physical education programs in selected Public Colleges in Chitwan, Nepal. It assesses intra-mural and extra-mural sports programs, sports budgets, infrastructure, and factors limiting student participation, ultimately providing recommendations for improvement. The research employed a survey-based methodology, with data collected from 21 physical education personnel and 21 college players who participated in inter-college competitions. A validated questionnaire covering multiple aspects of sports programs was used, and responses were analyzed using percentages and chi-square tests. Key findings indicate that although sports equipment quality is generally satisfactory, coaching, incentives, and female participation require significant improvement. Many institutions lack adequate sports facilities, coaching are irregular and financial incentives for student-athletes are insufficient. Gender disparities in sports participation remain prominent, with female students facing greater barriers to engagement. Additionally, heavy academic workloads negatively impact sports participation. To address these challenges, the study recommends increasing intramural competitions, enhancing financial incentives, expanding sports facilities, improving coaching programs, and integrating physical education into the academic curriculum. Targeted strategies for increasing female participation and scheduling sports activities without academic conflicts were also proposed. By implementing these measures, Public Colleges can create a more inclusive and effective physical education system that promotes holistic student development and long-term sports engagement.